Inorganic cadmium- and arsenite-induced malignant transformation of human bladder urothelial cells - Sens, Donald A; Park, Seongmi; Gurel, Volkan; Sens, Mary Ann; Garrett, Scott H; Somji, Seema (Toxicological sciences, 2004)
Arsenic and cadmium (Cd(+2)) are human carcinogens, and epidemiological studies have implicated both pollutants in the development of urinary bladder cancer. Despite this epidemiological base, it is unknown if either Cd(+2) or arsenite (As(+3)) can directly cause the malignant transformation of human urothelial cells. The goal of this study was to determine if Cd(+2) and/or As(+3) are able to cause the malignant transformation of human urothelial cells. The strategy employed was to expose the nontumorigenic urothelial cell line UROtsa to long-term in vitro exposure to Cd(+2) and As(+3), with the endpoint being the ability of the cells to form colonies in soft agar and tumors when heterotransplanted into nude mice. It was demonstrated that a long-term exposure to either 1 M Cd(+2) or 1 M As(+3) resulted in the selection of cells that were able to form colonies in soft agar and tumors when heterotransplanted into nude mice. The histology of the tumor heterotransplants produced by UROtsa cells malignantly transformed by Cd(+2) had epithelial features consistent with those of a classic transitional-cell carcinoma of the bladder. The histology of the tumor heterotransplants produced by cells malignantly transformed by As(+3) was unique in that the cells displayed a prominent squamoid differentiation.